Attaining multiple dispatch in widespread object-oriented languages (2014)
Multiple dispatch allows determining the actual method to be executed, depending on the dynamic types of its arguments. Although some programming languages provide multiple dispatch, most widespread object-oriented languages lack this feature. Therefore, different implementation techniques are commonly used to obtain multiple dispatch in these languages. We evaluate the existing approaches, presenting a new one based on hybrid dynamic and static typing. A qualitative evaluation is presented, considering factors such as software maintainability and readability, code size, parameter generalization, and compile-time type checking. We also perform a quantitative assessment of runtime performance and memory consumption.